1999
DOI: 10.1159/000010129
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Polyhydramnios, Estimated Fetal Weight and Preterm Delivery Are Independent Risk Factors for the Presenceof Congenital Malformation s

Abstract: Objective: To evaluate maternal and fetal factors associated with congenital malformations in patients with polyhydramnios. Study Design: The study group consisted of 275 singleton pregnancies with an amniotic fluid index (AFI) >25.0 cm. An equal number of controls were matched for maternal age, gravidity, parity and gestational age. The proportion of cases and controls with malformations was compared. Polyhydramnios cases were categorized into three groups by severity: mild (AFI 25–30 cm), moderate (AFI: 30.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 15 publications
2
31
1
Order By: Relevance
“…Anisa Fawad conducted a study where total number of cases of polyhydramnios was 70 and found congenital abnormality as anencephaly in maximum number of cases, duodenal atersia, oesophageal atresia and gastroschisis two each. 10,13 Present study subjects presented in 20-27 weeks of gestation were 3.3%, 28-36 weeks 6.6% and 37 -42 weeks 90% comparable tostudy done by Akram H, Nasir A, Rana T on increasing severity of polyhydramnios -a risk factor for congenital malformation conducted in Lady Willingdon hospital, Lahore presented with the result of subjects in 20-27 weeks of gestation were 10 (16.6%), in 28-36 weeks of gestation were 28 (46.6%) and in 37-42 weeks of gestation were 28 (46.6%) and in 37-42 weeks of gestation were 22 (36.6%). 15 In present study the probable aetiological factor for polyhydramnios was idiopathic in 65.1%, fetal congenital abnormality in 26.6% and gestational diabetes mellitus in 8.3%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anisa Fawad conducted a study where total number of cases of polyhydramnios was 70 and found congenital abnormality as anencephaly in maximum number of cases, duodenal atersia, oesophageal atresia and gastroschisis two each. 10,13 Present study subjects presented in 20-27 weeks of gestation were 3.3%, 28-36 weeks 6.6% and 37 -42 weeks 90% comparable tostudy done by Akram H, Nasir A, Rana T on increasing severity of polyhydramnios -a risk factor for congenital malformation conducted in Lady Willingdon hospital, Lahore presented with the result of subjects in 20-27 weeks of gestation were 10 (16.6%), in 28-36 weeks of gestation were 28 (46.6%) and in 37-42 weeks of gestation were 28 (46.6%) and in 37-42 weeks of gestation were 22 (36.6%). 15 In present study the probable aetiological factor for polyhydramnios was idiopathic in 65.1%, fetal congenital abnormality in 26.6% and gestational diabetes mellitus in 8.3%.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that with increasing severity of polyhydramnios, percentage of anomalous foetusincreases. 10 Perinatal morbidity and mortality are significantly increased when polyhydramnios is present at delivery. Fetal conditions that are associated with polyhydramnios include major congenital anomalies (open neural tube defects, upper gastrointestinal tract obstruction or malformation etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a growing amount of evidence has demonstrated a relationship between IUGR and macrosomic fetuses with short- and long-term complications [6,11,12,13,14]. The link between long-term cardiovascular and metabolic diseases has been studied and has shown a higher rate of hypertension, diabetes mellitus and cardiovascular risk in infants and adults who had extremely abnormal FG [1,2,19].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, most of attention has been given to fetuses located at the far sides of EFW curves because those cases account for most of the perinatal morbidity [6,10,11,12,13,14,15,16,17,18]…”
Section: Introductionmentioning
confidence: 99%
“…Polyhydramnios, defined as AFI greater than 24 cm, has been related to maternal diabetes [1][2][3] and has been involved in preterm labor [2,4] , congenital malformations [1][2][3][5][6][7] and macrosomia [1][2][3]8] . The term 'idiopathic hydramnios' is used to describe pregnancies where polyhydramnios is present, but without any ultrasono-graphically identifiable fetal anomalies or maternal diseases.…”
Section: Introductionmentioning
confidence: 99%